Pancreatic Pseudocyst with Colonic Perforation Complication - Angga Pramudita; Marcellus Simadibrata; Achmad Fauzi; Nisan Soeheri (The Indonesian Society for Digestive Endoscopy, 2011)
Pancreatic pseudocyst is one of complications of both acute and chronic pancreatitis. It is a rare clinical condition. The incidence is low ranging between 1.6 and 4.5%, or 0.5-1 per 100,000 adults annually. The clinical manifestations range from asymptomatic to severe acute abdomen due to complications. Acute complications may include bleeding, infection, rupture and perforation of the gastrointestinal tract; while chronic complications are gastric and biliary obstruction as well as thrombosis of portal vein. We present a case report of a 38-year-old male with complaints of abdominal pain, fatigue, nausea and vomiting containing undigested food and yellow liquid. On clilnical examination, the patient was found to be fatigue, having enlarged abdomen, unpalpable liver and spleen, no signs of shifting dullness was detected. We found an abdominal mass in the left upper and lower quadrant sized 20 x 10 cm accompanied with epigastric pain on palpation. Abdominal ultrasonography revealed a cystic lesion on the head of pancreas with differential diagnosis of pseudocyst. The abdominal computed tomography (CT-scan) showed a lesion arising from pancreas, extending into abdominal cavity and part of left groint and attaching to left intestinal in the abdomen, part of gastric region and left diaphragm. A diagnosis of pancreatitis was suspected with differential diagnosis of pancreatic mass and peritonitis. It is a case report of pancreatic pseudocyst with acute complication of colonic perforation. Keywords: pseudocyst, pancreatitis, pancreatitis complication, colonic perforation